Dorcus tianlongi, a new species from central China (Coleoptera: Lucanidae: Lucaninae) - Wang, Cheng-Bin; Zhou, Chao (Zootaxa, 2019)
A new species of stag beetle, Dorcus tianlongi Wang & Zhou, new species (Coleoptera: Lucanidae: Lucaninae) is described from Guizhou Province, China. It is closely related to D. liyingbingi Huang & Chen, 2013 and D. mencius (Kriesche, 1935). Diagnostic characters of the three species are illustrated and compared. Dorcus mencius is for the first time recorded from Henan Province of China.